Bunch technique for semionline with two groups of items - Kotov, Vladimir M.; Bogdanova, Natallia S. (Journal of the Belarusian State University. Mathematics and Informatics, 2019)
Bunch technique for semionline with two groups of items is proposed in this paper. Algorithm to solve this problem is to distribute items from the first group bunch approach and after that apply LS-algorithm to assign items from the se cond group. In order to prove the estimation of our algorithm is introduced different types of bunches to distribute all items from the first group such a way that only one of the entered types of bunches are obtained. During the second stage we use LS with worst case performance is at most 17/9.